Insulin like growth factor binding protein 7 (IGFBP7) expression is linked to poor prognosis but may protect from bone disease in multiple myeloma - Bolomsky, Arnold; Hose, Dirk; Seckinger, Anja; Lipp, Susanne (Journal of hematology & oncology, 2015)
Background: Insulin like growth factor binding protein 7 (IGFBP7) is a secreted protein binding insulin like growth factor 1 (IGF-1), insulin, vascular endothelial growth factor A (VEGFA), and activin A. It antagonizes bone morphogenetic proteins and is involved in the tumour propagation of solid as well as haematological malignancies. Its role in multiple myeloma (MM) is not defined so far. We therefore aim here to investigate its prognostic and pathophysiological role in MM. Methods:The clinical significance of IGFBP7 gene expression was investigated by gene expression profiling in two independent cohorts (n = 948) of newly-diagnosed MM patients. Methylation of the IGFBP7 promoter was analysed by pyrosequencing and treatment of MM cell lines with 5-aza-2-deoxycytidine. The impact of IGFBP7 on MM cells was studied by CCK-8 assay, BrdU assay and flow cytometry, respectively. IGFBP7 expression in bone marrow stromal cells (BMSCs) was studied by quantitative RT-PCR. For osteoblast development, immortalized and primary human BMSCs were cultured in osteogenic differentiation medium for 7-14 days in the presence of recombinant human IGFBP7 and/or activin A. Results:Median IGFBP7 expression is significantly lower in CD138-purified plasma cells from individuals with MGUS and MM, compared to normal bone marrow plasma cells. IGFBP7 gene expression in MM cells is regulated by methylation, shown by pyrosequencing and exposure to demethylating agents (5-aza-2-deoxycytidine). High expression of IGFBP7 in MM cells is associated with adverse survival in two independent cohorts of 247 and 701 newly-diagnosed MM patients treated with high-dose therapy and autologous stem cell transplantation. IGFBP7 is associated with prognostically adverse chromosomal aberrations (t(4;14) and gain of 1q21), MMSET expression, and higher myeloma cell proliferation. In vitro, IGFBP7 overcomes activin A induced osteoblast suppression and promotes osteogenesis. MM cells downregulate IGFBP7 in stromal cells, possibly contributing to the osteoblast suppression found in MM. Conversely, higher IGFBP7 expression is associated with a lower probability of myeloma bone disease. Conclusions: Our data indicate that IGFBP7 expression is a marker for a specific methylation pattern in myeloma, linked to translocation t(4;14) associated MMSET expression, showing clinical features of adverse prognosis with absence of myeloma bone disease. Electronic upplementary material: The online version of this article (doi:10.1186/s13045-014-0105-1) contains supplementary material, which is available to authorized users.